JARING SEBAGAI SUBSTRAT BUATAN PENEMPELAN SPORA Porphyra sp DI PERAIRAN NEGERI HUKURILA - Tuahatu, Juliana W; Lokollo, Frijona F (Pattimura University, 2022)
Hukurila waters have the potential to develop a macro type of algae Porphyra sp. The technique of casting a net that is used as an artificial substrate as a place for sticking spores is interesting to experiment with, which has always only utilized this Porphyra from nature during the eastern season. This activity aims to apply the technique of making artificial subsrats using nets in increasing Porphyra yields. The activity began with the planting of pieces of wood as long poles to tie the net. After the piles have been well embedded then, the net is then opened and tied at every angle from the net to the wooden pole using nylon rope. At the end of this activity, it was seen that there was an understanding of the use of nets as an artificial substrate for pasting Porphyra spores. This activity is very beneficial for the community in increasing the number of crops through the technique of making artificial substrates as a medium for sticking spores during the eastern season